PEMANFAATAN MEJA PAYUNG PANEL SURYA UNTUK KEBUTUHAN LISTRIK DAN PENINGKATAN PRODUKTIVITAS KOLAM PANCING DI DESA SIDOPEKSO - Karim, Abdul; Sulistiyanto; M. Mahbubi (Jurnal Bakti Masyarakat Indonesia, 2025)
Sidopekso Village, Kraksaan District, Probolinggo Regency, has potential in the fisheries sector, one of which is through the Podho Joyo Fishing Pond business. However, this business faces constraints such as limited electricity, high operational costs, and suboptimal business management. To address these challenges, the Nurul Jadid University community service team implemented a program using the Solar Panel Umbrella Table as a renewable energy source and supporting technology for fishing pond management. The program implementation method includes five stages: (1) outreach to partners regarding the benefits of renewable energy and digital technology; (2) training on solar power plant (PLTS) use, water quality monitoring, and digital marketing; (3) technology implementation through the installation of the Solar Panel Umbrella Table, installation of water quality sensors, and implementation of digital marketing strategies; (4) mentoring and evaluation of implementation effectiveness; and (5) a sustainability program through continued training and the development of standard operating procedures. The program results show that the Solar Panel Umbrella Table can supply daily electricity needs for lighting, aeration, and water filtration with operational cost savings of approximately 40%. Water quality sensors help managers monitor pond conditions in real time, ensuring fish health. Management has begun using digital record-keeping and social media promotions, resulting in a 20% increase in visitor numbers within the first month. In conclusion, the implementation of renewable energy technology and digitalization of business management has successfully improved Podho Joyo Fishing Pond's energy efficiency, productivity, and competitiveness. This program can serve as a model for developing fisheries businesses based on clean energy and appropriate technology, supporting the achievement of the Sustainable Development Goals (SDGs) in the areas of energy, economics, and innovation.